PENDAMPINGAN KEMANDIRIAN TPA AZ-ZAHRA BERBASIS PEMASARAN SOSIAL - ike arisanti (Universitas Lancang Kuning, 2019)
Tempat Pengasuhan Anak (TPA) Az-Zahra is a childcare center that was established in 2011 under the leadership of the Aisyiyah area of ​​Malang. Lots of Child Care Centers in Malang are able to offer competent facilities, facilities and infrastructure as well as managers. Servants have solutive suggestions related to marketing that can be done by partners, namely by creating websites and marketing through social media. Besides social marketing can also be done by holding parenting activities that also invite potential customers who are around the Az-Zahra landfill. This program is carried out jointly with the hope that the results generated from this program can be directly measured and evaluated by partners and service as a basis for the success of the predetermined achievements. In addition, the evaluation results are also used as a basis for assistance in subsequent programs.